Models of industrial policy: Driving innovation and economic growth - Andrea Dugo; Fredrik Erixon; Oscar Guinea (European Centre for International Political Economy (ECIPE), 2025)
Europe's approach to industrial policy has undergone a dramatic transformation in recent years, with state aid reaching 1.4 per cent of GDP in 2022, levels unseen since the early 1990s. While advocates of substantial state aid argue that this intervention is necessary to maintain competitiveness in a world where the US and China are implementing large-scale industrial strategies, the effectiveness of this approach remains contested. This paper critically examines the evolution of EU industrial policy, contrasting it with alternative models adopted globally and within Europe itself. While EU economic strategies since the 1980s had focused mainly on horizontal policies such as market liberalisation, competition enforcement and support to Research and Development (R&D), recent developments have shifted towards a more interventionist stance. This shift has largely been driven by crises - the financial crisis of 2008, the COVID-19 pandemic, geopolitical tensions, and the energy transition - which have prompted calls for greater state involvement in shaping industrial outcomes. However, this paper shows that, while industrial policy can support good economic development, it is not a determinant of economic success. All successful economies have pursued industrial policy, but so have all unsuccessful ones. This suggests that industrial policy, in and of itself, is not a determinant of economic growth and competitiveness. The effectiveness of industrial policy depends on its design, its ability to avoid market distortions, and its capacity to stimulate genuine private-sector investment rather than crowding it out [...]
Keywords: 330; Industriepolitik; EU-Industriepolitik; EU-Staaten; Welt